EFEKTITIFAS PROGRAM PEMBINAAN KEDISIPLINAN DALAM PROSES BELAJAR MENGAJAR TERHADAP ETOS KERJA MANDIRI GURU DI SDN 11 KAMPUNG TARANDAM - Ernawati, Ernawati (STKIP Pesisir Selatan, 2018)
Based on the results of observations that researchers have conducted teachers at SDN 11 Kampung Tarandam, it was found that the ability of teachers to arrange to increase the effectiveness of teaching and learning activities is still low. The purpose of this study was to describe and obtain information about the Effectiveness of the Discipline Development Program in the Teaching and Learning Process for Teachers' Independent Work Ethics at SDN 11 Kampung Tarandam. This research is a school action research. The research procedures in this study include planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 13 elementary school teachers at SDN 11 Kampung Tarandam. The research data was collected using observation sheets. Data were analyzed using percentages. The results of the study show that with a disciplinary training program in the teaching and learning process to improve the teacher's work ethic at SDN 11 Kampung Tarandam. This is evidenced by the existence of disciplinary guidance in the learning process. Improving the teacher's work ethic at SDN 11 Kampung Tarandam from cycle I to cycle II. The average ability of students and teachers in increasing the effectiveness of learning activities in the first cycle is 48 with less categories and in the second cycle is 82.66 in the good category